Demographic Diversity and Faultlines: The Compositional DYnamics of Organizational Groups - Lau, Dora C.; Murnighan, J. Keith (Academy of Management Review, 1998)
In this article we address issues of diversity within organizational groups by discussing and summarizing previous approaches and by introducing a new variable—faultlines—which depends on the alignment of individual member characteristics. By analyzing a group's faultlines, we focus attention on the underlying patterns of group member characteristics, which can be an important determinant of subgroup conflict, particularly when the group's task is related to one of its faultlines. We discuss the dynamics of faultlines from the early to later stages of a group's development and show how they may be strongest and most likely when diversity of individual member characteristics is moderate.